Pengaruh Penyapihan Anak Usia 1-6 bulan Terhadap Pertumbuhan Di Kelurahan Sragen Kulon Kecamatan Sragen Kabupaten Sragen - Warnani, Amalina Indah; Budinugroho, Agus Taria (Jurnal Berita Ilmu Keperawatan, 2017)
Breast milk is the natural first food from babies, but not all babies are breastfeed. Breast milk contains all the energy and nutrients that the baby needs. But in reality not all mothers breastfeed exclusively to his son at the age of 1-6 months. Mothers with weaning has its own assessment why do weaning. purpose of this research aim to know correlation weaning of early age child (1-6 months) with growth in Sragen Kulon village of Sragen. This research is non-experimental, descriptive comparative research design. Taking data use used cross-sectional approach. Sample are children early weaning yet for age (1-6 months) are: 30 children. Sample of children who performed early weaning age (1-6 months) are 32. Sampling was carried out on children who are not weaning using simple random sampling method. Weaning children performed using total sampling. Research instrument using a tape measure and a scale to determine the child's growth. Data analysis use Fisher exact test. Results there is impact weaning of early age child (1-6 months) with growth in Sragen Kulon village of Sragen. adverse impact on early childhood (1-6 months) 84,4%. of children who were weaned early have normal growth and 86,7% of children who are not weaned also have normal growth. There is no correlation weaning of early age child (1-6 months) with growth in Sragen Kulon village of Sragen with p-value = 0.798.